2023
DOI: 10.2188/jea.je20210242
|View full text |Cite
|
Sign up to set email alerts
|

Change in the Estimated Glomerular Filtration Rate Over Time and Risk of First Stroke in Hypertensive Patients

Abstract: Background The association between changes in estimated glomerular filtration rate (eGFR) over time and the risk of stroke remains inconclusive. We aimed to evaluate the relation of eGFR change during the China Stroke Primary Prevention Trial (CSPPT) with the risk of first stroke during the subsequent post-trial follow-up. Methods A total of 11,742 hypertensive participants with two eGFR measurements (median measure interval, 4.4; interquartile range, 4.2–4.6 years) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…Previous studies have reported associations of dynamic decline in kidney function and cardiovascular events [7–10] and mortality [8,10,11,14–17]. Our study of large (>30%) or rapid (>5 ml/min/1.73 m 2 /year) eGFR decline being robustly related to major cardiovascular events and all-cause mortality is consistent with prior research [7–11,14–17], but such findings regarding stroke are inconsistent [6–9]. Shlipak et al .…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Previous studies have reported associations of dynamic decline in kidney function and cardiovascular events [7–10] and mortality [8,10,11,14–17]. Our study of large (>30%) or rapid (>5 ml/min/1.73 m 2 /year) eGFR decline being robustly related to major cardiovascular events and all-cause mortality is consistent with prior research [7–11,14–17], but such findings regarding stroke are inconsistent [6–9]. Shlipak et al .…”
Section: Discussionsupporting
confidence: 85%
“…Another study found that greatest decline of at least 5 ml/min/1.73 m 2 /year was related to 29% increase of stroke risk after adjusting for baseline eGFR [9], while He et al . [6] reported declining eGFR (≥5% per year) was associated with a higher risk of first stroke. To our knowledge, only one article has examined the relationship between change in eGFR and recurrent stroke; that of Vart et al .…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations